Long-term, health-enhancing physical activity is associated with reduction of pain but not pain sensitivity or improved exercise-induced hypoalgesia in persons with rheumatoid arthritis - Monika Löfgren; Christina H. Opava; Ingrid Demmelmaier; Cecilia Fridén; Ingrid E. Lundberg; Birgitta Nordgren; Eva Kosek (Arthritis Research & Therapy, 2018)
Abstract Background We aimed to evaluate the 1-year and 2-year outcome of a health-enhancing physical activity (HEPA) support program on global pain, pressure pain sensitivity, and exercise-induced segmental and plurisegmental hypoalgesia (EIH) in persons with rheumatoid arthritis (RA). Methods Thirty participants (27 women and 3 men) were recruited from a larger intervention cohort that engaged in strength training and moderate-intensity aerobic activity. Assessments were performed before the HEPA intervention and at 1-year and 2-year follow-ups. Global pain was assessed on a visual analogue scale (0–100). Pressure pain thresholds (PPTs) and suprathreshold pressure pain at rest corresponding to 4/10 (medium pain) (SP4) and 7/10 (strong pain) (SP7) on Borg CR 10 scale were assessed by algometry. In a subsample (n = 21), segmental and plurisegmental EIH were assessed during standardized submaximal static contraction (30% of the individual maximum), by algometry, alternately at the contracting right M. quadriceps and the resting left M. deltoideus. Results Global pain decreased from before the intervention to 2-year follow-up (median 11 to median 6, P = 0.040). PPTs and SP4 pressure pain at rest did not change from before the intervention to 2-year follow-up, while SP7 decreased from mean 647 kPa to mean 560 kPa (P = 0.006). Segmental EIH during static muscle contraction increased from the assessment before the intervention (from mean 1.02 to mean 1.42, P = 0.001), as did plurisegmental EIH (from mean 0.87 to mean 1.41, P <0.001). There were no statistically significant changes in segmental or plurisegmental EIH from before the intervention to 2-year follow-up. Conclusion Participation in a long-term HEPA support program was associated with reduced global pain, whereas pressure pain sensitivity at rest was not reduced and EIH did not change. Thus, our results do not favor the hypothesis that long-term HEPA reduces pain by improving descending pain inhibition in persons with RA. Trial registration ISRCTN25539102, ISRCTN registry, date assigned March 4, 2011. The trial was retrospectively registered.